Sensitivity Analysis of the Dynamic Behaviour of Agricultural Machines - Clijmans, Luc; Ramon, Herman; de Baerdemaker, Josse (agricultural engineering.eu, 1997)
Even during normal operation of agricultural machines a number of disturbances occur that can generate excessive Vibration Ievels. The disturbances can come from soil roughness or from rotating elements within the machine. Machine Vibrations affect the manual or automatic controls and they reduce the efficiency of the operations to be carried out like for example spraying. ln this contribution, an experimental modal model is derived that contains the eigenfrequencies and mode shapes of the machine. A frequency sensitivity analysis on the modal model gives information about the most critical locations on the structure with respect to local parameter changes. ln a later stage, this is used to predict frequency shifts owing to structural modifications like local stiffness and inertia changes.